Associação entre restrição de sono e sobrepeso/obesidade entre crianças do sul do Brasil: estudo de uma coorte de nascimentos - Halal, Camila dos Santos El (2014)
Introduction: Pediatric obesity has become a worldwide public health concern, with a perspective of an even greater increase over the next years, especially among developing countries. Overweight children are exposed from an early age to comorbidities and chronic pathologies that imply on an increase in morbimortality. Concomitantly, the general population, including children, has been sleeping gradatively less time. Studies have been searching for evidence linking sleep deprivation to overweight or obesity. Among pre-school children, this correlation is not well established. Objective: To evaluate the relation between sleep deprivation in the first years of life and overweight or obesity at 4 years of age. Materials and Methods: We used the data from the Pelotas, Brazil, 2004 birth Cohort, corresponding to perinatal, 12, 24 and 48 months follow-ups. On these moments, the child´s main caretaker responded to questions regarding sleep and feeding habits, as well as socioeconomic and demographic characteristics. Children who slept for less than 10 hours per night were considered sleep deprived. Children with a BMI Z-score 2 standard deviations above limits established by the World Health Organization were considered overweight, and those with a BMI Z-score above 3 standard deviations were considered obese. Results: Of the 4263 live births in Pelotas during the study year, 4231 were enrolled in the study. Of those, 94%, 93.5% and 92% were re-evaluated on the 12, 24 and 48-month follow-ups, respectively. On the analysis stratified by age, only at 24 months we found a positive association between sleep deprivation and overweight at 48 months (PR 1,731. CI95% 1,246; 2,406. P=0,001). Analyzing the relation between sleep deprivation at any moment during the study period, we found that sleep-deprived children had a 27% higher chance of overweight/obesity at the end of the study (RP 1,267. CI 95% 0,989;1,624). This association was maintained after adjusting for possible confounders. Conclusion: On the studied population, children with sleep deprivation between 12 and 48 months of age showed a higher chance of being overweight or obese at 4 years. These findings show the importance of sleep quality and sleep hygiene in prevention and management of overweight and obesity in childhood.